SOCIOCULTURAL CONTEXT OF A PERSONALITY FORMATION - Пономаренко, Я. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the features of influence of sociokultur open up on forming of personality in an informative era